Neutralization of the CD95 ligand by APG101 inhibits invasion of glioma cells in vitro. Issue 7 (August 2015) - Merz, Christian; Strecker, Alexander; Sykora, Jaromir; Hill, Oliver; Fricke, Harald; Angel, Peter; Gieffers, Christian; Peterziel, Heike
Abstract : Glioblastoma is a disease characterized by rapid invasive tumour growth. Studies on the proapoptotic CD95/CD95L signalling pathway recently suggested a significant contribution of CD95 signalling towards the high degree of motility in glioma cells. Apogenix has developed APG101, a clinical phase II compound designed to bind and neutralize CD95L, and thus to interfere with CD95/CD95L-based signalling. APG101 has shown clinical efficacy in a controlled randomized phase II trial in patients with recurrent glioma. Because APG101 is not cytotoxic to tumour cells in vitro, we postulated that the anti-invasive function of APG101 is the main mechanism of action for this compound. Using three-dimensional spheroid invasion assays in vitro and in murine brain tissue cultures, we found that knockdown of endogenous CD95L reduced the invasive phenotype in our two glioblastoma model cell lines U87-MG and U251-MG. Invasion was restored in CD95L knockdown cells upon the addition of soluble recombinant CD95L and this effect was inhibited by APG101. We conclude that CD95L from autocrine and paracrine sources contributes towards the invasive phenotype of glioblastoma cells and that APG101 acts as a suppressor of proinvasive signalling by the CD95/CD95L pathway in glioblastoma. Abstract : Supplemental Digital Content is available in the text.